2013
DOI: 10.1016/j.soard.2013.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Assessment of Bariatric Surgery (LABS): Retention strategy and results at 24 months

Abstract: Background Retaining participants in observational longitudinal studies following bariatric surgery is difficult yet critical because the retention rate affects interpretation and generalizability of results. Strategies for keeping participants involved in such studies are not commonly published. Objective To review LABS retention strategies and present the 24-month retention data Methods The LABS Consortium monitors an observational cohort study of 2458 adults enrolled prior to bariatric surgery at 10 cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 32 publications
1
30
0
1
Order By: Relevance
“…2,13,14 Nevertheless, most major RYGBP series have shown a 60-50% postoperative follow-up rate at 1 year, which drops off dramatically with time. 15 These estimates are similar to the overall adherence prevalence of 51% (95%CI: 44.5-57.5%) during the 18-month follow-up period of our study.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…2,13,14 Nevertheless, most major RYGBP series have shown a 60-50% postoperative follow-up rate at 1 year, which drops off dramatically with time. 15 These estimates are similar to the overall adherence prevalence of 51% (95%CI: 44.5-57.5%) during the 18-month follow-up period of our study.…”
Section: Discussionsupporting
confidence: 88%
“…Several authors argued that patients who stop attending postsurgical visits shortly after surgery might differ from patients who are lost to follow-up later in the multidisciplinary care program. 4,15 Evaluating early and late attrition separately when analyzing adherence factors may be particularly pertinent to further explore this issue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This difficulty in long-term patient follow-up has plagued bariatric surgical outcomes research, particularly retrospective analyses. A study from the Longitudinal Assessment of Bariatric Surgery (LABS) identified key strategies to address this problem of patient retention, including honoraria, travel reimbursement, providing patient progress reports, continual updating of patient contact information, and standardized scheduling and patient contact protocols [35]. Future efforts should focus on these strategies to improve patient participation and optimize reporting of results.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Moreover, poor retention in postoperative bariatric aftercare has detrimental effects on patient safety due to delayed diagnosis of complications and also on unbiased and internal and external research study results. 13 Most bariatric surgery centers have standardized patient postoperative aftercare protocols, but regardless, patient attrition is a consistent problem in the field, particularly beyond 1 year after surgery. 14 The literature reports that follow-up rates can be as low as 50% at 1 year, 12,15 30% at 2 years, and < 10% at 10 years after surgery.…”
Section: Introductionmentioning
confidence: 99%